DISTRIBUTION OF NATURAL AND ANTHROPOGENIC RADIONUCLIDES IN SURFICIAL SEDIMENTS OF JAKARTA - Ali Arman Lubis (BATAN, 2006)
The concentration and distribution of natural and anthropogenic radionuclide in surficial sediments of Jakarta Bay were investigated with the aim of evaluating its level and environmental radioactivity. Sediments were sampled in 30 locations using Smith-McIntyre Grab sampler. Sediments were dried, homogenized and sealed for 1 month for equilibration and for the detection, analysis and data acquisition, a high purity germanium (HPGe) detector coupled with a high resolution multichannel analyzer (MCA) was used. Additionally, the grain sizes were analyzed by means of hydrometer. The result shows that the specific activity of 238U, 226Ra, 232Th, 40K and 137Cs range from 6.71±1.01 Bq/kg to 28.63±4.29 Bq/kg, 6.46±0.97 Bq/kg to 28.21±4.23 Bq/kg, 16.62±2.49 Bq/kg to 40.46±6.07 Bq/kg, 115.80±12.16 Bq/kg to358.69±30.49 Bq/kg, and 0.03±0.01 Bq/kg to 1.99±0.34 Bq/kg with the average value are 12.83±2.11 Bq/kg, 12.03±1.98 Bq/kg, 26.55±4.36 Bq/kg, 235.55±19.37 Bq/kg, and 0.77±0.13 Bq/g, respectively. It shows that the activity of radionuclides in the research area are in natural level and the variation may be influenced by the grain size distribution in the sample. The absorbed dose rate and radium equivalent of gamma radiation was estimated to be 32.06±7.72 nanoGrey/h and 68.14±11.20Bq/kg, respectively.